A systematic approach to assessing the sustainability of the Renewable Energy Standard (RES) under the proposed American Renewable Energy Act (H.R. 890). (25th August 2009) - Eason, Tarsha N.; Owusu, Yaw A.; Chapman, Hans
Assessing sustainability is a complex challenge for policy makers, scientists and engineers. In an effort to evaluate industrial systems, a range of alternative methods have been developed; unfortunately, these methods stop short at demonstrating how industrial activity affects sustainability. In response to this need, the Population based Model for Assessing Sustainability Implications (PMASI) was developed through a systematic view of the factors affecting sustainability. This paper provides background on the method development and implementation of the approach for evaluating scenarios of the USA energy sector in accordance with the RES standard proposed in the American Renewable Energy Act (H.R. 890).